From protection to reduction? The impact of the public health insurance scheme on child labour in Ghana - Christoph Strupat (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Using the fourth and fifth wave of the Ghanaian Living Standard Household Survey, I empirically investigate whether the implementation of the National Health Insurance Scheme affects child labour in Ghana. My findings suggest that the implementation of the insurance scheme leads to a decrease in out-of-pocket payments for health purposes, which is linked to a substantial reduction in the incidence of child labour. Furthermore, I find that the overall reduction in child labour is strongest in rural areas and the agricultural sector. I conclude that the provision of public health insurance improves the financial protection of households, which removes the necessity for households to send their children to work. Thus, health insurance schemes seem to be an effective social protection instrument to fight child labour.
Keywords: 330; Armut und Ungleichheit; Soziale Sicherung und Inklusion